The Teaching of Writing Skills in An EFL Online Classroom at A Secondary School: Between Bandwidth and Immediacy - Agung Ginanjar Anjaniputra; Ilma Fitriyana (Ma'soem University, 2023)
Despite the need for online classrooms, the scarcity of studies in online writing classes leads to the limitation of the modes of learning in writing classes. This study portrays the learning of EFL writing in online classrooms by delving into different modes that the teacher used. This study is carried out by employing a qualitative approach. The data were collected by using students’ reflective journals and semi-structured interviews. The participants of the study were 35 students of the twelfth grade and one English teacher. As the data from the students’ journal and the interview were categorized into broader themes, the teaching and learning activity was compatible with modes of online classrooms in Modes 1 and 2 which were low bandwidth-low immediacy and low bandwidth-high immediacy. This denotes low bandwith as the preferred mode used by the teacher, presumably due to the technical access and supports. Thus, English teachers can implement interesting media for teaching and learning depending on the availability of the learning sources by sticking to the availability of online learning modes. For the students, students can ask the teacher if they encounter difficulties in online classrooms.